Comparative Analysis of Insect Pest Diversity in Cocoa (Theobroma cacao L.) Agroecosystems under Different Shade Tree Canopies: Papaya vs. Banana - Basroh Saepul Mubarok; Ramadhani Mahendra Kusuma; Noni Rahmadhini (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study compared the pest insect community structure in cocoa plantations shaded by papaya and banana trees. The study was conducted from January to March 2025 using systematic sampling in six cocoa fields, consisting of three papaya-shaded and three banana-shaded plantations. In each field, 19 traps were installed, comprising nine yellow traps, nine pitfall traps, and one light trap, supported by visual observations. Pest insects were identified to the genus level, and community structure was assessed using diversity (H′), evenness (E′), richness (R′), and dominance (C′) indices. Banana-shaded cocoa fields supported slightly more pest insect genera than papaya-shaded fields, with 22 and 21 genera recorded, respectively. Banana-shaded plots also showed higher diversity, evenness, and richness, accompanied by lower dominance. These patterns indicate that the denser banana canopy may create more heterogeneous microhabitat conditions that support a broader range of pest insects. Shade tree type influences pest insect community structure in cocoa plantations. Banana shade was associated with a more diverse and balanced pest insect community, whereas papaya shade showed relatively higher dominance, suggesting a greater risk of specific pest outbreaks. These findings highlight the importance of shade tree selection in integrated pest management, particularly for designing site-specific monitoring and targeted control strategies in cocoa plantations.